Determinant Factors affecting Quality of Life of Children with HIV/AIDS - Candra Maulana; Irwanto; Dominicus Husada (Indian Journal of Forensic Medicine & Toxicology, 2022)
HIV/AIDS causes physical problems, such as recurrent infections, growth disorders and malnutrition.HIV/AIDS also causes psychosocial problems, such as being shunned by friends and gettingdiscriminatory behavior. All of the problems described earlier affect children’s mental growth anddevelopment which will affect the quality of life of children with HIV/AIDS.This research is a cross sectional study, conducted at the Intermediate Care Unit of Infection Disease ofChildren Outpatient Clinic in Dr. Soetomo General Hospital Surabaya and Voluntary Counselling andTesting Outpatient Clinic in Gresik General Hospital, Probolinggo General Hospital and TrenggalekGeneral Hospital in November 2019-May 2020. Data collected was descriptively, then statisticallyanalyzed by bivariate and multivariate analysis.According to bivariate analysis, factors significantly related to quality of life of children with HIV/AIDS were age, monthly caregiver income, distance between diagnosis and therapy, immunologicalstatus, nutritional status and treatment adherence. Multivariate analysis showed that age (p=0,014,Odds Ratio [OR] 18,780, confidence interval [CI] 1,810-194,844) and treatment adherence (p=0,010,OR 7,823, CI 1,631-37,516) had a significant relationship with the quality of life of children with HIV/AIDS (p <0.05).In conclusion, age, monthly caregiver income, distance between diagnosis and therapy, immunologicalstatus, nutritional status and treatment adherence are significantly related to the quality of life of childrenwith HIV/AIDS. Age and treatment adherence have the most significant relation with the quality of lifeof children with HIV/AIDS .